Comportamento e desempenho bioeconômico de ovinos em capim-tanzânia sob duas frequências e duas intensidades de pastejo - Mochel Filho, William de Jesus Ericeira (2013)
The behavior and economical and productive performance of lambs (Morada Nova breed ½ x ½ undefined breed) weighing 19.36 ± 3.23 kg and 185 ± 50 days old grazing Tanzaniagrass under two frequencies (FD) and two intensity (ID) defoliation (85 and 95% of interception of photosynthetically active radiation - IRFA , and residual leaf area index - IAFr 1.0 and 1.8 , respectively) in a factorial arrangement 2x2 (includes six periods of the day in the case of behavioral assay) in a completely randomized design with four replications (paddocks or lambs) were evaluated. Data were subjected to analysis of variance, mean test and descriptive statistics. The lowest time spent in shade occurred on the management 85x1.8. The highest time spent grazing occurred in FDs 85% with an average of 621.8 min/d (minutes/day). The lambs expend more time in rumination activities in the lowest grazing frequencies managements. There was no effect on idling time, but there was influence of FDs in time spent with other activities. In the FDs 85% were spent 60.3 min/d, compared to 111.0 min/d in 95% FDs. There was no influence of the frequency of FDs ingestion of salt water and defecation of the animal. The frequency of urination was higher in sheep kept in pastures with FD 95%. The higher bit rate occurred in FDs 95%. The longest time spent in shade occurred between 11:00 and 14:59h . The animals preferentially grazed during the day, with peaks of grazing between 07:00 and 10:59h and between 15:00 and 18:59h. The frequency of urination, defecation and water demand showed no significant variations throughout the day. It must be stressed the low water demand observed in general. There was no interaction between FD and ID in the average daily gain (ADG), where the IRFA 85% and the ID of 1.8 showed higher ADG (89.2 g/animal x day). The FDs of 85 and 95% provided stocking rates of 74 and 96 animals/ha, respectively. The management 85x1.8 provided higher yield of body weight of 2421 kg/ha x year. The pastures under management 85x1.8 provided the highest average daily gain and the highest yield of body weight per unit of area. The activity gross income (R$/month) was superior in the 85x1.8 management. The effective operating cost (COE) activity (R$/month) was higher in the management 85x1.8 totalizing 2.71 herds/year with a COE of R $ 11,493.68. The management 85x1.8 showed profit of R$ 4,130.44/month, compared to R$ 106.75 in the 95x1.0 management. The management 85x1.8 presented lower COE, TOC and TC, R$4.73; 5.06 and 5.10/kg of body weight, respectively. The best benefit/cost occurred in the management 85x1.8, which also led to higher ADG, higher turnover of lots and higher profit per kg of body weight. The use of genetic with greater earning potential groups can decrease the size needed to have an economically viable area, increase the turnover of the system and generate greater profitability.